Landscaping on or near Septic Drain Fields - Whitney C Elmore; William Lester; James Moll; Andrea Albertin; Mary Lusk (EDIS, 2020)
Septic systems are common throughout most rural areas, and their care and maintenance are essential to the health of people, wildlife, livestock, agricultural commodities, and water resources. One way to ensure optimal performance of your septic system is to landscape appropriately near the drain field. The purpose of this new 3-page publication of the UF/IFAS Department of Soil and Water Sciences is to provide landscape management guidance for septic system drain fields. Information presented here will be useful for homeowners, landscape management professionals, and Extension agents who work in horticulture, natural resources, agriculture, and family services. Written by Whitney C. Elmore, William Lester, James Moll, Andrea Albertin, and Mary Lusk. https://edis.ifas.ufl.edu/ss687